The Development of Junior High School English Materials from Contextual Teaching and Learning Perspective: Participatory Research and Development - Hikmah Pravitasari (English Didactic, 2019)
The objectives of this study were: (1) to investigate the quality of the existing course book used in Islamic Junior High School, and (2) the development of Contextual Writing Book. This research was conducted at SMP Muhammadiyah Boarding School Prambanan. This research was categorized into Research and Development (R D). It was conducted in two steps, including exploration and development. The exploration step consisted of literature review, field study, need analysis, and product planning while the development step comprised prototype development, field testing, and final product. Data reduction, data display, and conclusion proposed in Miles and Huberman’s model was used to analyze the data. After conducting needs analysis through interview, questionnaire, observation, and document analysis, the researcher concluded that there was a need of supplementary English material to fulfil the students’ needs toward the material at Junior High School. The existing course book did not provide sufficient writing assignment and focused on speaking assignment only, instead of four English skills that were required. In development stage, the researcher designed a prototype of Contextual Writing Book referring to Contextual Teaching and Learning (CTL) approach. Then, it was validated and reviewed by five experts. To get the feasible product, the prototype was implemented three times in the classroom. The final try out, class observation, questionnaire, and Focus Group Discussion (FGD) approved the draft’s feasibility and appropriateness as supplementary material to teach students of Junior High School.